Comparative analysis of Cf-4 and Cf-19 in tomato (Solanum lycopersicum) – A bioinformatics study - TANDON, GITANJALI; SINGH, SATENDER; KAUR, SUKHDEEP (The Indian Journal of Agricultural Sciences, 2017)
Tomatoes (Solanum lycopersicum L.), a model fruit crop, are largely affected by leaf mould disease, caused by an Ascomycete (Cladosporium fulvum) leading to significant economic loss across the globe. Though many R genes corresponding to this disease, viz. Cf-2, Cf-4, Cf-5, Cf-6, Cf-9 and Cf-19 are reported but such studies are confined to genomic level rather than proteomic level. Since host parasite interaction occurs at protein level thus in the present study, attempt has been made to carry out the studies of these R genes at proteomic level. Protein sequences of Cf-4 and Cf-19 genes were used for sequence analysis by Conserved Domain Database followed by construction of their three-dimensional models using Modeller. The obtained models were further validated and finalized protein models of both the genes were compared with the help of DALI Server. The present study revealed that there was 89% sequence identity between these proteins whereas they were confined to 78% only at structural level. Model generated from the present study can be used in interaction studies between Cf-4 and Cf-19 and their corresponding avirulence (Avr) protein. Such study would lead to better understanding of genetic basis of susceptibility of the tomato plants to the invading pathogen. This can also help in establishing them as putative candidate gene, which are desirable in development of disease resistant tomato varieties, combating pathogen attack in endeavour of tomato improvement program.